1983
DOI: 10.1083/jcb.97.6.1834
|View full text |Cite
|
Sign up to set email alerts
|

Molecular morphology of the tetrodotoxin-binding sodium channel protein from Electrophorus electricus in solubilized and reconstituted preparations.

Abstract: The appearance of detergent-solubilized voltage-regulated sodium channel protein was recently characterized by this laboratory. Negative-staining revealed rod-shaped particles measuring 40 X 170 A. Further studies have suggested that the actual configuration of this protein may be quite different from the rod-shaped structures. Freeze-fracture and freeze-etch images of the protein in reconstituted membranes indicated that the channel is cylindrical with a diameter of 100 A and a minimum length of 80 A. Experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1984
1984
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…The evidence of Na+ channel accumulation on end bulb axolemma is consistent with our prior light and electron microscopic evidence of Na+ channel immunolocalization in neuromas in the lateral line nerve of Apteronotus using fish-specific anti-Na+ channel antibodies (Devor et al, 1989). Likewise, since Na+ channels yield large-diameter intramembranous particles (IMPS) in freeze-fracture replicas (Ellisman, 1979;Ellisman et al, 1983;Rosenbluth, 1983;Small et al, 1984;Stricharz et al, 1984) it is consistent with the observed shift of IMP sizes in rat neuroma end bulb axolemma to larger values (Fried et al, 1991).…”
Section: Neuroma End Bulbssupporting
confidence: 86%
“…The evidence of Na+ channel accumulation on end bulb axolemma is consistent with our prior light and electron microscopic evidence of Na+ channel immunolocalization in neuromas in the lateral line nerve of Apteronotus using fish-specific anti-Na+ channel antibodies (Devor et al, 1989). Likewise, since Na+ channels yield large-diameter intramembranous particles (IMPS) in freeze-fracture replicas (Ellisman, 1979;Ellisman et al, 1983;Rosenbluth, 1983;Small et al, 1984;Stricharz et al, 1984) it is consistent with the observed shift of IMP sizes in rat neuroma end bulb axolemma to larger values (Fried et al, 1991).…”
Section: Neuroma End Bulbssupporting
confidence: 86%
“…The concept of an evolutionarily related neuronal ion channel gene family (25) is, however, supported by a number of biochemical, pharmacological, and morphological observations: (i) the overall or subunit molecular masses of the neuronal ion channels analyzed so far are very similar (25); (ii) many different drugs are known that affect several types of channel proteins (ref. 26; unpublished data); and (iii) recent electron microscope analysis suggests an astounding similarity between the molecular morphology of the nicotinic acetylcholine receptor and the voltage-dependent sodium channel isolated from fish electric organ (27,28). In our view, all of these structural and functional relationships between the different neuronal ion channels are highly suggestive of a common evolutionary root of this class of membrane proteins (25).…”
Section: Discussionmentioning
confidence: 62%
“…2, lanes 4-7, and Table 2). In other experiments, the major common peptides obtained with V8 protease (28,15, and 11 kDa) were digested further with chymotrypsin. This resulted in the production of three or four peptide fragments of the same apparent molecular mass (19,17,11, and 9 kDa) from all three glycine receptor polypeptides (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…The size distribution and freeze-fracture pattern suggest that some of these particles may be the (Na + +K+)ATPase (Skriver et al, 1980) or the voltagesensitive sodium channel (Ellisman et al, 1983), two macromolecules concentrated along normal nodal axolemma (Ellisman & Levinson, 1982;Ariyasu et al, 1985).…”
Section: Introductionmentioning
confidence: 98%